Cerebrospinal fluid–suppressed T2‐weighted MR imaging at 7 T for human brain. Issue 5 (19th November 2018) - Pan, Jullie W.; Moon, Chan Hong; Hetherington, Hoby P.
Abstract : Purpose: T2 ‐weighted lesional imaging is most commonly performed using inversion recovery turbo spin echoes. At 7 T, however, this acquisition is limited for specific absorption rate and resolution. This work describes and implements a method to generate CSF‐suppressed T2 ‐weighted imaging. Methods: The strategy uses a driven equilibrium spin‐echo preparation within an inversion recovery with multiple 3D gradient‐echo imaging blocks. Images are combined using the self‐normalization approach, which achieves CSF suppression through optimized timing of individual blocks and minimizes sources of variation due to coil receptivity, T2 *, and proton density. Simulations of the magnetization‐prepared fluid‐attenuated inversion recovery gradient‐echo (MPFLAGRE) method over T1 and T2 relaxation values are performed, and in vivo demonstrations using an 8 × 2 transceiver array in healthy controls are shown. Results: The specific absorption rate of the calculated MPFLAGRE sequence is 11.1 ± 0.5 W (n = 5 volunteers), which is 74 ± 2% of the US Food and Drug Administration guidelines. This method acquires both contrasts for CSF suppression with detection of long T2 components and T2 ‐weighted imaging in a single acquisition. In healthy controls, the former contrast generates increased signal in the cortical rim and ependyma. A comparison is shown with a conventional 3D SPACE fluid‐attenuated inversion recovery acquisition, and sensitivity to pathology is demonstrated in an epilepsy patient. Conclusion: As applied with the 8 × 2 transceiver, the MPFLAGRE sequence generates both whole‐brain contrast suitable for lesional and T2 ‐weighted imaging at 7 T in fewer than 10 minutes within the US Food and Drug Administration's specific absorption rate guidelines.